Benign and Malignant Brenner Tumors Show an Absence of TERT Promoter Mutations That Are Commonly Present in Urothelial Carcinoma. (September 2016) - Khani, Francesca; Diolombi, Mairo L.; Khattar, Pallavi; Huang, Weihua; Fallon, John T.; Epstein, Jonathan I.; Zhong, Minghao
Abstract : Brenner tumors are uncommon ovarian neoplasms, which have morphologic and immunophenotypical features of transitional cell (urothelial) differentiation. The origin of Brenner tumors is perplexing, but they are believed to arise from transitional cell metaplasia occurring within the ovary and/or fallopian tube, although it is controversial whether this metaplasia is truly along transitional cell lines. Recently, TERT promoter mutations have been identified in urothelial carcinoma (UC) with high frequency (approximately 70%), and the current literature suggests a potential diagnostic and/or prognostic role of these mutations in UC. Molecular evidence supporting that Brenner tumors represent neoplasms exhibiting transitional cell differentiation is scant. To explore this further, we investigated a series of 19 Brenner tumors of the ovary (15 benign and 4 malignant) for the presence of TERT promoter mutations after genomic DNA extraction from formalin-fixed paraffin-embedded tissue blocks and standard polymerase chain reaction sequencing. TERT promoter mutations were not identified in any of the cases (0/19). The absence of TERT promoter mutations in Brenner tumors suggests that despite the morphologic and some immunophenotypical resemblance to non-neoplastic and neoplastic transitional epithelium, Brenner tumors may exhibit a molecularly distinct pathogenesis. The findings also may portend diagnostic utility in rare cases wherein it is difficult to distinguish a primary malignant Brenner tumor of the ovary from metastatic UC.